2003
DOI: 10.1210/en.2002-221076
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxin Lesion of Hypothalamically Projecting Norepinephrine and Epinephrine Neurons Differentially Affects Circadian and Stressor-Stimulated Corticosterone Secretion

Abstract: Hindbrain norepinephrine (NE) and epinephrine (E) neurons play a pivotal role in the central distribution of sensory signals derived from the internal environment. Their projections influence the various secretory patterns of the hypothalamo-pituitary-adrenal axis and are essential for feeding and adrenal medullary responses to glucoprivation. NE and E terminals in the paraventricular nucleus of the hypothalamus (PVH) and associated hindbrain cell bodies can be virtually eliminated by PVH microinjection of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
160
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(179 citation statements)
references
References 73 publications
17
160
0
Order By: Relevance
“…Because these responses also occur after intravenous 2-DG and insulin (Ritter et al, 2003;Khan and Watts, 2004;Gorton et al, 2006;Rapp et al, 2006), our data show that NE is sufficient for recapitulating neuroendocrine responses to these glycemic challenges. Moreover, because hindbrain CA afferents are necessary for these responses (Ritter et al, 2001(Ritter et al, , 2003Rapp et al, 2006), NE appears both sufficient and necessary for CRH neuroendocrine neurons to respond to glycemic challenges. Supporting this, local PVH or systemically delivered 2-DG trigger NE release in the PVH vicinity (McCaleb and Myers, 1982;Peinado and Myers, 1987;Nagatani et al, 1996).…”
Section: Pvh-injected Ne Recapitulates Neuroendocrine Responses To Glsupporting
confidence: 55%
See 2 more Smart Citations
“…Because these responses also occur after intravenous 2-DG and insulin (Ritter et al, 2003;Khan and Watts, 2004;Gorton et al, 2006;Rapp et al, 2006), our data show that NE is sufficient for recapitulating neuroendocrine responses to these glycemic challenges. Moreover, because hindbrain CA afferents are necessary for these responses (Ritter et al, 2001(Ritter et al, , 2003Rapp et al, 2006), NE appears both sufficient and necessary for CRH neuroendocrine neurons to respond to glycemic challenges. Supporting this, local PVH or systemically delivered 2-DG trigger NE release in the PVH vicinity (McCaleb and Myers, 1982;Peinado and Myers, 1987;Nagatani et al, 1996).…”
Section: Pvh-injected Ne Recapitulates Neuroendocrine Responses To Glsupporting
confidence: 55%
“…Establishing these linkages requires, in part, identifying afferents signaling the PVH during glycemic challenge and the neurotransmitter(s) involved in such signaling. Ritter et al (2001) identified an essential afferent pathway by showing that selectively destroying PVH afferents originating from hindbrain CA cell groups impaired the feeding and PVH responses to 2-DG or insulin challenges (elevated CRH hnRNA, Fos mRNA, and circulating corticosterone) but not those occurring basally or from forced-swim challenge (Ritter et al, 2003). These lesions also impair PVH phospho-ERK1/2 responses to insulin (Rapp et al, 2006).…”
Section: Phospho-erk1/2 Tracks Crh Neuron Activation During Glycemic mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies endorse anti-DBH-saporin as a tool for achieving focal aminergic denervation by ablating the neurons that project to targeted terminal fields (Ritter et al, 2003;Schiltz and Sawchenko, 2007). The approach exploits the fact that DBH on the inner surface of synaptic vesicles is exposed to the extracellular space during transmitter release, providing a target for antiserum to bind the enzyme, and toxin to be internalized, in the normal course of vesicle recycling (Wrenn et al, 1996).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…This was achieved by comparing the effects of selectively lesioning noradrenergic inputs to the mPFCd on indices of acute stress-induced PVH activation (Fos protein, CRF mRNA) and pituitary-adrenal hormonal output. Lesions were performed by the focal administration of an axonally transported immunotoxin, anti-dopamine-␤-hydroxylase-saporin (anti-DBH-saporin), which targets specifically noradrenergic terminals and the neurons that give rise to them (Wrenn et al, 1996;Ritter et al, 2001Ritter et al, , 2003. Ancillary analyses were also performed to assess the impact of noradrenergic denervation of mPFCd on stress-induced activational responses in both the mPFC and LC.…”
Section: Introductionmentioning
confidence: 99%